2006
DOI: 10.1128/jvi.80.4.1915-1921.2006
|View full text |Cite
|
Sign up to set email alerts
|

Core Protein of Pestiviruses Is Processed at the C Terminus by Signal Peptide Peptidase

Abstract: The core protein of pestiviruses is released from the polyprotein by viral and cellular proteinases. Here we report on an additional intramembrane proteolytic step that generates the C terminus of the core protein. C-terminal processing of the core protein of classical swine fever virus (CSFV) was blocked by the inhibitor (Z-LL) 2 -ketone, which is specific for signal peptide peptidase (SPP). The same effect was obtained by overexpression of the dominant-negative SPP D 265 A mutant. The presence of (Z-LL) 2 -k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…Sequential processing results in discrete intermediate products, which sometimes have functions that the terminal products do not have, and thus provides a means for regulating functions needed at different stages of the virus infectious cycle. The cellular protease SPP has been co-opted by HCV, the closely related GB virus B and Classical swine fever virus for maturation of their core proteins [13,18,42]. Recent data in the HCV model have shown that SPP-catalysed liberation of mature core protein is required for production of infectious progeny virus at a step which remains to be defined, perhaps related to coupling of viral genome replication and virus assembly [19,33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sequential processing results in discrete intermediate products, which sometimes have functions that the terminal products do not have, and thus provides a means for regulating functions needed at different stages of the virus infectious cycle. The cellular protease SPP has been co-opted by HCV, the closely related GB virus B and Classical swine fever virus for maturation of their core proteins [13,18,42]. Recent data in the HCV model have shown that SPP-catalysed liberation of mature core protein is required for production of infectious progeny virus at a step which remains to be defined, perhaps related to coupling of viral genome replication and virus assembly [19,33].…”
Section: Discussionmentioning
confidence: 99%
“…Signal peptides are indicated by hatched boxes. The scissors indicate the sites of cleavages catalysed by SP; the arrowheads indicate the sites proposed for the cleavage catalysed by signal peptide peptidase (SPP) to liberate p21 [14][15][16][17][18][19]. The sequence at the C-terminus of core protein is presented for the wild-type HCV strains of genotype 1a and 1b used in this study.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…HCV core is processed further by SPP within the h-region of the signal sequence to generate a mature product, which is considered to participate in virion morphogenesis (30). SPP cuts also in an analogous position in classical swine fever virus (CSFV), a pestivirus that is related to HCV (31). To determine whether GBV-B core is a substrate for SPP, a polyprotein encompassing GBV-B core to the N-terminal region of NS2 and including an epitope tag inserted within the core sequence (Fig.…”
Section: Gbv-b Core Protein Is Processed By Spp-mentioning
confidence: 99%
“…Nevertheless, a recent study [62] indicated that recombination between strains is possible. The ORF is translated into a single polypeptide of about 3900 amino acids which is co-and post-translationally processed into mature peptide by a number of virus and host encoded proteases [63,64,65,66]. The virion is made up of 4 structural proteins viz., C, Erns, E1 and E2 which are encoded at the 5' end of the genome.…”
Section: A Few Salient Features Of the Structure Composition And Funmentioning
confidence: 99%